The "Golden Worship" Tradition: A Sociological Study of Islamic Law in Traditional Marriages of the Lembak Tribe Community, Bengkulu - Suwarjin Suwarjin (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2021)
This research examines the implementation of the Emas Sembah tradition in traditional marriages of the Lembak tribe in Bengkulu from the perspective of Urf. This research is motivated by sociological problems that occur in the form of the husband's inability to carry out the tradition to the belief that bad karma will occur if he does not carry out the tradition. This research is qualitative research with a normative-sociological approach. Primary data was taken from traditional leaders, religious leaders, and husband and wife who carried out the Emas Sembah tradition. The study results show that the tradition of giving gold for worship is included as urf fasid because it contains more negative values and impacts than positive ones. Among the negative values and impacts are the husband's inability to pay gold for worship, the assumption that virgins are marked by bleeding when having intercourse between husband and wife, misunderstanding in determining virginity, no strong evidence in determining virginity, exposing the wife's disgrace to society, belief in karma it is bad if you do not practice Emas Sembah, Manipulation of virginity, Opening up the wife's shame if she is not a virgin, The integrity of the household is threatened if it is known that the wife is not a virgin. Penelitian ini mengkaji pelaksanaan tradisi “Emas Sembah” dalam pernikahan adat masyarakat suku Lembak di Bengkulu dari perspektif Urf. Penelitian ini dilatar belakangi oleh problem sosiologis yang terjadi berupa ketidaksanggupan pelaksanaan tradisi oleh pihak suami hingga keyakinan terjadinya karma buruk jika tidak melaksanakan tradisi. Penelitian ini adalah penelitian kualitatif dengan pendekatan normatif-sosiologis. Data primer diambil dari tokoh adat, tokoh agama, suami-istri yang melakukan tradisi “Emas Sembah”. Hasil penelitian menunjukkan bahwa tradisi pemberian “Emas Sembah” ini termasuk urf fasid karena mengandung nilai dan dampak negatif lebih banyak dari pada nilai dan dampak positifnya. Di antara nilai dan dampak negatifnya adalah Ketidaksanggupan pihak suami terhadap besaran “Emas Sembah”, anggapan perawan ditandai dengan keluar darah ketika berhubungan suami istri, Kesalahpahaman dalam penentuan keperawanan, Tidak ada alat bukti yang kuat dalam penentuan keperawanan, Terbukanya aib istri ke masyarakat, Keyakinan akan Karma buruk jika tidak melaksanakan “Emas Sembah”, Manipulasi keperawanan, Membuka aib istri jika tidak perawan, Keutuhan rumah tangga terancam jika diketahui istri tidak perawan.